Faktor Penentu Pemberian ASI Eksklusif di Desa Gampa, Kabupaten Aceh Barat - Agustina, Dilla; Khairunnas, Khairunnas; Muliadi, Teuku; Muhsin, Sriwahyuni (Polyscopia, 2024)
Breast milk is recognized as the optimal source of nutrition for infants, particularly during the early stages of life. The World Health Organization (WHO) recommends exclusive breastfeeding for the first six months of life, followed by complementary feeding while continuing breastfeeding for up to two years. The Johan Pahlawan Health Center reported one of the lowest rates of exclusive breastfeeding coverage in West Aceh District in 2020, at 24.7%. This study aims to identify factors associated with exclusive breastfeeding practices among mothers in Gampa Village, Johan Pahlawan District, West Aceh Regency. Employing a cross-sectional research design with a quantitative approach, data for dependent and independent variables were collected simultaneously. A purposive sampling method was used, and statistical analysis was conducted using the Chi-Square test with a significance level of ?=0.05. The findings revealed that among 34 respondents, 30 mothers (88.2%) provided exclusive breastfeeding, while 4 mothers (11.8%) did not. The study concluded that variables such as education, occupation, and knowledge of exclusive breastfeeding are significantly related to breastfeeding practices, whereas age showed no significant relationship with exclusive breastfeeding in the study population.